Hakikat Wahyu Perspektif Manna Al-Qathan - Qimanullah, Abdul Malik; Sanah, Siti (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
The Qur'an is a holy book and the main source of teachings for Muslims containing the word of Allah SWT, revealed to the Prophet Muhammad SAW as revelation through the intermediary of the Angel Gabriel. The process of receiving the revelation is unique and exclusive, occurring when the Prophet is conscious or through a real dream. Revelation, in this context, is fundamentally different from inspiration and instinct, although all three can be understood as forms of "supernatural calling." Revelation is specific and only addressed to prophets and apostles, while inspiration and instinct are psychological processes that can be experienced by ordinary humans. This study uses a qualitative approach with a literature study method, which includes analysis of interpretations, classical Islamic literature, and the views of contemporary scholars, to explore the meaning of revelation and distinguish it from inspiration and instinct conceptually and theologically.